The Effect of Financial Performance on Return on Asset Venture Capital Industry in Indonesia - Alfiana,; CM Simatupang, Ervina; Nurani, Nina; Kaniawati, Keni; Maya Dora, Yenny (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to find out which financial performance influences the profitability of the venture capital industry in Indonesia. The data used are secondary data from the Indonesian finance institution statistics source from the Venture Capital Company Monthly report from 2015-2018, with internal performance used being operational efficiency ratio, investing and financing to assets ratio, gearing ratio, and non-performing financing, while profitability uses return on assets. The results of the study indicate that only the investing and financing to assets ratio has a positive effect on return on investment in the venture capital industry. The results of this study are useful for the government to see how venture capital increases its profitability to help many businesses and micro, small, and medium enterprises that are not yet bankable to obtain business funds, business guidance, and technical assistance. This research is also useful for the financial services authority in making policies regarding the limits of investing and asset ratio in the venture capital industry, as well as useful for venture capital practitioners in investing and financing to increase return on assets and useful for growing investment to investee companies, expanding, gaining extra profits, and accompaniment, guidance, and interchanging expertise in managing businesses from venture capital companies.